Q. 1 D4.5( 14 Votes )

# <span lang="EN-US

Answer :

Consider two binomials as m2−n2 and m + n

Now, to get the product of two binomials ) m2−n2 and m + n we use the

distributive law i.e. (m2−n2)×( m + n) = m2(m) + m2(n)-n2(m)-n2(n) =

m3 + m2n-mn2-n3

Therefore , the product of m2−n2 and m + n is m3 + m2n-mn2-n3.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics